HUBUNGAN INISIASI MENYUSUI DINI (IMD) DENGAN KEJADIAN PERDARAHAN POST PARTUM DI PUSKESMAS ONAN HASANG TAHUN 2023 - Sinaga, Suharni Pintamas; Tampubolon, Elmina (JURNAL ILMIAH DHDT - KEBIDANAN, 2024)
The Ministry of Health (2008) states that IMD involves pressing the newborn up against the mother's chest or stomach, let him to wiggle about in search of the nipple, and then nursing him until he is full. At least the first hour following the baby's birth is dedicated to this procedure. This kind of study uses a cross-sectional design and is descriptive correlative in nature. It measures both the independent and dependent research variables concurrently throughout the course of one time period. The purpose of this study is to examine the correlation between the occurrence of postpartum hemorrhage at the Onan Hasang Community Health Center in 2023 and the Early Breastfeeding Initiation (IMD). There were 26 persons (81.3%) postpartum. Respondents who did not initiate early breastfeeding (IMD) represented the minority with postpartum hemorrhage, i.e. 3 (9.4%). Based on the study results obtained, there is a relationship between early initiation of breastfeeding (IMD) and the incidence of postpartum bleeding at Onan Hasang Community Health Center in 2023, which from the main trial Fisher's exact test, the obtained p value is 0.008, which is less than 0.05. This means that the earlier you start breastfeeding (IMD), the less postpartum bleeding you will have. We note that the majority of respondents who completed Early Initiation of Breastfeeding (IMD) did not experience postpartum bleeding, i.e. 26 (81.3%). The majority of respondents who did not initiate early breastfeeding (IMD) had postpartum hemorrhage, i.e. 3 (9.4%). Fisher's exact test results showed a p-value of 0.008 < 0.05. This means that the alternative hypothesis (Ha) of this study is accepted, i.e. there is an association between early initiation of breastfeeding (IMD) and the incidence of postpartum hemorrhage at community health centers. Onan Hasang coin in 2023.